High-volume hospitals are associated with lower mortality among high-risk emergency general surgery patients. Issue 3 (September 2018) - Ogola, Gerald O.; Crandall, Marie L.; Richter, Kathleen M.; Shafi, Shahid
Abstract : INTRODUCTION: We have previously demonstrated that Emergency General Surgery (EGS) patients treated at high-volume hospitals experience lower mortality rates than those treated at low-volume hospitals. However, EGS comprises a wide spectrum of diseases. Our goal was to determine which EGS diseases had better outcomes at high-volume hospitals. METHODS: We undertook a retrospective analysis of the National Inpatient Sample database for 2013 (a nationwide representative sample). Patients with EGS diseases were identified using American Association for the Surgery of Trauma definitions. A hierarchical logistic regression model was used to measure risk-adjusted probability of death, adjusting for age, sex, race, ethnicity, insurance type, and comorbidities. Patients were then grouped into 16 risk groups based upon their predicted probability of death. We then compared observed mortality rates at high- versus low-volume hospitals within each risk group. RESULTS: Nationwide, 3, 006, 615 patients with EGS diseases were treated at 4, 083 hospitals in 2013. Patients with predicted risk of death of 4% or higher (275, 615 patients, 9.2%) had lower observed mortality rates at high-volume hospitals than at low-volume hospitals (7.7% vs. 10.2%, p < 0.001). We estimated that 1, 002 deaths were potentially preventable if high-risk patients who were treated at low-volume hospitals were instead transferred to high-volume hospitals. CONCLUSION: EGS patients with predicted risk of death of 4% or higher experience lower mortality rates at high-volume hospitals than at low-volume hospitals. A regional system of EGS care that enables rapid transfer of high-risk patients to high-volume hospitals may prevent several deaths. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III; Therapeutic/Case Management, level IV. Abstract : Supplemental digital content is available in the text.